STRATEGI DINAS PENDIDIKAN KABUPATEN BUNGO DALAM MENCEGAH DEKADENSI MORAL MELALUI PROGRAM PENGUATAN PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Al-Ihsan, M. Iqbal; Urip Sulityo; Eddy Haryanto (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
This study aims to analyze the strategy of the Bungo Regency Education Office in preventing moral decadence through the implementation of the Character Education Strengthening Program (PPK) in elementary schools. The research method used is a qualitative approach with a descriptive design. Data collection techniques were carried out through interviews, observations, and documentation with informants from the Education Office, school principals, and teachers. Data analysis used an interactive model that includes data reduction, data presentation, and drawing conclusions. The results show that the strategies implemented include formulating character-based policies, strengthening teacher capacity through training, integrating character values ​​into learning, and strengthening school culture. However, program implementation still faces obstacles such as budget constraints, lack of ongoing training, and weak synergy with parents. Efforts made include improving cross-sector coordination, optimizing program evaluation, and strengthening collaboration with the community. This study implies that the success of character education requires a systemic and collaborative approach between local governments, schools, and families.   Keywords: Character Education; Moral Decadence; Educational Strategy; Elementary School; Educational Policy.